The Influence of City Branding, E-Wom, Attractiveness, and Accessibility on The Decision to Visit Madiun City - Kadi, Dian Citaningtyas Ari; Apriyanti; Pratama, Ryan Surya; Fauzi, Rizal Ula Ananta (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
This study aimed to determine the influence of City Branding, e-WOM, Attraction, and accessibility on the decision to visit tourist attractions in Madiun City. The research method used in this study is quantitative, using a sample of 385 respondents with the help of SPSS25 software. The study results indicate that the city branding variable (X1) partially positively and significantly influences the decision to visit Madiun City, so the first hypothesis is accepted. Partially, the e-wom variable (X2) positively and significantly influences the decision to visit Madiun City, so the second hypothesis is accepted. Partially, the attractiveness variable (X3) positively and significantly influences the decision to visit Madiun City, so the third hypothesis is accepted. Partially, the variable of accessibility (X4) positively and significantly influences the decision to visit Madiun City, so the fourth hypothesis is accepted.